The Co-Evolution of Economic and Political Development - Huang, Fali (Institutional Knowledge at Singapore Management University, 2006)
This paper establishes a simple model of long run economic and political development, which is driven by the inherent technical features of different factors in production, and political conflicts among factor owners on how to divide the outputs. The main capital form in economy evolves from land to physical capital and then to human capital, which enables the respective factor owners (landlords, capitalists, and workers) to gain political powers in the same sequence, shaping the political development path from monarchy to elite ruling and finally to full suffrage. When it is too costly for any group of factor owners to repress others, political compromise is reached and economic progress is not blocked; otherwise, the political conflicts may lead to economic stagnation.